PENGARUH BERBAGAI JENIS MEDIA TANAM TERHADAP PERKEMBANGBIAKAN FUNGI MIKORIZA ARBUSKULA DENGAN MENGGUNAKAN TANAMAN INANG KACANG HIJAU (Vigna radiata L.) - Yuni Amelia Ika Putri Agus; St Subaedah; Andi Ralle (Percetakan Umi Toaha Makassar, 2022)
This study was conducted to determine the effect of various types of growing media on the proliferation of arbuscular mycorrhizal fungi using mung bean host plants. This research was conducted at the Greenhouse, Faculty of Agriculture, Universitas Muslim Indonesia, and the Laboratory of Microbiology, Research, and Development Center for Environment and Forestry. The study started from April to August 2021. This study was compiled based on a completely randomized design consisting of four treatments of growing media, namely: soil, soil + raw husk, soil + husk charcoal, and soil + raw husk + husk charcoal. Each treatment was repeated 3 times so that 12 experimental units were obtained, and each experimental unit used 3 polybags so that there were 36 polybags in all. The results showed that the difference in planting media had an effect on the proliferation of arbuscular mycorrhizal fungi. Soil growing media obtained the highest arbuscular mycorrhizal fungal infection, namely 76.11%, and the number of spores, 49.33. The growth of the host plant (mung bean) was better in soil + husk charcoal as indicated by the number of leaves of 17 pieces, a root length of 37.66 cm, and a root volume of 2.33 ml.